Pengaruh Pembiayaan Bermasalah Sebagai Antisipasi Terhadap Krisis Perbankan Pada PT. Bank Muamalat Indonesia Cabang Mataram - Ismail, Ismail; Andriani, Fifi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research is motivated by the growth rate of financing in Islamic banks, the object of this research is PT. Bank Muamalat Indonesia Mataram Branch with financing data classified as problematic from 2019 to 2020 was substandard, doubtful and stuck. The collectability rate has increased and decreased in different ways over the past 2 years.The results of this study based on the partial test (t test) that was carried out, the results showed that non-performing financing had a negative and significant effect on the profitability of PT. Bank Muamalat Indonesia means that if the financing problem is PT. Bank Muamalat Indonesia is high then profitability will decrease and vice versa. For the second variable, operational efficiency also has a negative and significant effect on the operations of PT. Bank Muamalat Indonesia. means that when the level of non-performing financing is higher, it will automatically affect the level of profitability, if the NPF increases then profitability decreases. Based on the results of simultaneous hypothesis testing (Test F), states that financing problems and operational efficiency have a simultaneous effect on the profitability of PT. Bank Muamalat Indonesia with a significant value of 0.000033 <0.05 (5%), so that the independent variables, namely financing problems and operational efficiency simultaneously affect the profitability of PT. Bank Muamalat Indonesia Mataram Branch. The method used in this research is a descriptive quantitative method. The data in this study were obtained through primary data and secondary data. The data analysis technique in this study used the test statistics, partial hypothesis testing (t test) and simultaneous hypothesis testing (F test).